The history of the Riverside Church in the city of New York - Paris, Peter J. (Religion, race, and ethnicity, 2004)
Riverside Church and the development of 20th century American Protestantism / James Hudnut-Beumler -- Preachers for all seasons : the legacy of Riverside's free pulpit / Leonora Tubbs Tisdale -- A Christian vision of unity : an architectural history of the Riverside Church / John Wesley Cook -- Universal in spirit, local in character : the Riverside Church and New York City / Judith Weisenfeld -- The public witness of the Riverside Church : an ethical assessment / Peter J. Paris -- Congregations within a congregation : contemporary spirituality and change at the Riverside Church / Lawrence H. Mamiya